Vanillin Alleviates High Fat Diet-Induced Obesity and Improves the Gut Microbiota Composition - Guo, Jielong; Han, Xue; Zhan, Jicheng; You, Yilin; Huang, Weidong (Frontiers in Microbiology, 2018)
Vanillin, a simple phenolic compound, exists marginally in some plants and can be produced by microbes. Here we used high fat diet induced obese mice to study the effect of vanillin on obesity and obtained positive results: (1) decreased both body and adipose tissue weight; (2) ameliorated the disorders of blood parameters including ALT, LDH, glucose and so on and improved the insulin sensibility and glucose tolerance; (3) reduced the elevated level of inflammatory factors including LPS, IL-6 and TNF-α in plasma and liver tissue caused by obesity; and (4) enhanced the production of short chain fatty acids. Additionally, study results also demonstrated that vanillin significantly alleviated obesity-related gut microbiota disorders including the decrease of alpha- and beta-diversity. Furthermore, vanillin decreased the abundance of Firmicutes phylum, increased the richness of Bacteroidetes and Verrucomicrobiota phyla and inhibited the expansion of the lipopolysaccharide-producing bacteria Bilophila genus and the H2S-producing bacteria Desulfovibrio genus.